Extraction of total flavonoids from Chaenomeles speciosa (Sweet) Nakai and its antioxidant and lipoxygenase inhibition effects - Wenqing Pei; Yuting Sun; Juan Li; Yupei Zhang; Chenkang Jian; Feng Lu; Ali Tao; Qizhao Li (PLoS ONE, 2025)
Ultrasound-assisted extraction technology was utilized to extract total flavonoids from Chaenomeles speciosa (Sweet) Nakai, and response surface methodology was employed to optimize the extraction process. The anti-oxidant and lipoxygenase inhibitory activities were evaluated, along with an analysis of the type of inhibition. The results revealed that the optimal extraction conditions for total flavonoids from Chaenomeles speciosa (Sweet) Nakai were as follows: an ethanol concentration of 62%, a liquid-to-solid ratio of 15:1 mL/g, an ultrasonic temperature of 68°C, and an ultrasonic time of 40 min, resulting in a total flavonoid extraction rate of 10.18%. Antioxidant assays demonstrated that the Chaenomeles speciosa (Sweet) Nakai extract exhibited significant radical scavenging activities against 1,1-diphenyl-2-picrylhydrazyl radicals, 2,2’-azinobis (3-ethylbenzothiazoline-6-sulfonic acid ammonium salt) radicals, and hydroxyl radicals, with IC50 values of 582 µg/mL, 538 µg/mL, and 1709 µg/mL, respectively. Furthermore, enzyme inhibition assays indicated that the Chaenomeles speciosa (Sweet) Nakai extract possesses notable inhibitory activity against lipoxygenase, with an IC50 value of 2658 µg/mL. This inhibition is mediated through a mixed reversible inhibition mechanism.